2013
DOI: 10.1111/jam.12160
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Loop-mediated isothermal amplification combined with colorimetric nanogold for detection of the microsporidianEnterocytozoon hepatopenaeiin penaeid shrimp

Abstract: Aims: Enterocytozoon hepatopenaei is an emerging microsporidian parasite that has been linked to recent losses caused by white faeces syndrome (WFS) in cultivated giant or black tiger shrimp Penaeus (Penaeus) monodon and whiteleg shrimp Penaeus (Litopenaeus) vannamei in Asia. To more accurately assess its impact on shrimp production and to determine reservoir carriers for control measures, our objective was to establish a loop-mediated isothermal amplification (LAMP) assay combined with colorimetric nanogold (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…In the nested PCR step, both methods had identical sensitivity at 10 copies per reaction vial (Fig 3B), similar to what had previously been reported for the SSU-PCR method [23]. …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In the nested PCR step, both methods had identical sensitivity at 10 copies per reaction vial (Fig 3B), similar to what had previously been reported for the SSU-PCR method [23]. …”
Section: Resultssupporting
confidence: 84%
“…However, for those without equipment to carry out the process, an isothermal loop mediated (LAMP) method with a sensitivity of 2 EHP copies/reaction vial of total DNA from EHP-infected shrimp has been reported [23]. In this study, we found that the SSU-PCR and SWP-PCR methods could detect DNA plasmids containing respective target sequences at 10 copies per reaction vial, although the SWP-PCR method had better sensitivity than the SSU-PCR method for the first PCR step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once there is bacteria universal gene, the oligonucleotides conjugated with gold nanoparticles will hybridize with its target sequence that brings the gold nanoparticles together. Thus, the color of the liquid will change after hydrochloric acid addition due to the light absorption properties of nanoparticles, which is usually referred as the redshift effect (Aslan et al, 2004;Bakthavathsalam and Rajendran, 2012;Ploschner et al, 2012;Suebsing et al, 2013). For this purpose, thiol chemically modified 16S oligonucleotides conjugated with gold nanoparticles was prepared according to a protocol reported in a previous study (Hill and Mirkin, 2006) before the onchip assay.…”
Section: Preparation Of Gold Nanoparticle-conjugated 16s Probesmentioning
confidence: 99%
“…Then, the 20-nm gold nanoparticle conjugated 16S probes were added to hybridize the singlestrand DNA at 58°C. After 0.01 N hydrochloric acid was added into the test tubes, the colors of samples with bacterial genome DNA turned into red due to the red shift effect of gold nanoparticle particles (Suebsing et al, 2013) while the color of negative control stayed in purple, which was the original color of labeled gold nanoparticle probes. Therefore, by observing the colors of samples and comparing it with that of the negative control, the existence of bacteria could be confirmed.…”
Section: Detection Of Live Bacteria Using Gold Nanoparticles-conjugatmentioning
confidence: 99%